Primary osteoliposarcoma of the bone - Padua Michelle; Bhandari T.P.S; Pingle Jairamchander (Wolters Kluwer Medknow Publications, 2009)
Osteoliposarcoma are rare tumors of the bone. To our knowledge, so far only eight cases have been reported. Some of the reports have referred to these tumors as malignant mesenchymoma. We report a case of a male with osteoliposarcoma of the right femur who presented with pain and restricted movements of the right knee joint. Radiologically, a tumor in the lower end of the right femur was seen extending into the soft tissue. The biopsy was reported as osteosarcoma. The patient received three cycles of neo-adjuvant chemotherapy followed by limb-salvage surgery with provisions for a custom-made prosthesis. A histopathological study of the excision specimen revealed areas of pleomorphic liposarcoma with numerous osteoblasts associated with areas of osteoid surrounded by neoplastic cells. The final diagnosis was osteoliposarcoma. Only 21% tumor necrosis (effects of chemotherapy) was observed. Presently, 26 months following diagnosis, the patient is fine with no evidence of local recurrence or distant metastasis.